Libyan Crisis 2014-2018: The Conflict of the Internal Political and Social Forces and the Failure of the Political Solution - Al-Afef, Ahmad Khlaif; Mahafza, Mohammed Abdel-Karim; Al-Afif, Ahmad Husein; Gogazeh, Ziyad Mohammad (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to analyze the impact of the state of conflict and lack of harmony between the internal Libyan political and social forces, on the continuity and development of the Libyan crisis 2014-2018, and the failure of all political initiatives proposed to solve it. Methods: The subject was studied through the analytical descriptive approach based on analyzing the data and statements issued by the active forces in the course of the crisis, and its alignment with the reality of the course of events . Results: The study showed that the main factor in the continuity and the development of the Libyan crisis is related, in the first place, to the rejection of all the internal Libyan conflict forces, specially the Islamic and liberal ones of all the proposed political agreement attempts, and the endeavor of each of them to monopolize power and exclude the other, and the rejection of the principle of polititical pluralism. Conclusions: The Libyan crisis 2014-2018 was formed by what Libya inherited after the 2011 revolution, embodied by a weak authority that was unable to impose state sovereignty on all parts of the country, This led to the ignition of conflict between all internal political and social Libyan forces and the spread of civil war. The intervention of greedy foreign powers, especially the European power, helped in its development. They were looking forward to dominating Libyan wealth.